El hexágono de la investigación (2015)
This article does a review about the different theories, concepts and definition used in the design and development of academical frameworks, with the objective to strenghten the research culture and to promote the research spirit as part of the integral formation in both students and academical community in general. This review includes a look at philosophical theories as premises of developed research projects, and approaches, techniques, methods and instruments used in the research activity. Nowadays, these aspects are very important due to it is a time in which the quality of education is highly promoted. Although this work addresses a basic issues about research, focusing in the construction of a “research hexagon”, which interrelates the diversity of used terms by different authors in their publications about this process.